Pengaruh keahlian dan independensi terhadap kualitas audit dengan orientasi etika dan pengalaman kerja sebagai variabel moderasi pada BPKP Riau - Hengki Wijora; Emrinaldi Nur DP; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Audit quality is a complex its concept and difficult to understand, so that there is an error in determine the nature and quality. This is proved from the many research with many dimensions of audit quality. The purpose of this research is to explore the influence of expertise in auditing and independence to audit quality with ethical orientation and work experience as moderation variable. The population in this research is auditors of BPKP Riau. The sampling design of this research is purposive sampling with the final sample 47 auditors. This research used primary data by dissemination of the questionnaire conducted auditors of BPKP Riau. Used in this research as technical analyse for test hypothesis multiple linear regression and MRA. The results of this research showed that expertise and independence significant influence to audit quality, while ethical orientation and work experience as moderation variables proved unable to influence relationship expertise and independence to audit quality.Keywords : Expertise, Independency, Ethical Orientation, Work Experience, Audit Quality